PENERAPAN PENDEKATAN PEMBELAJARAN PAKEM DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 002 BAGAN BESAR - Elvi Zahara (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
The background of this research is the lack of students' mathematics learning outcomes. The low yield caused by the learning of mathematics teaching is so very boring, monotonous, stressful and meaningless. Departing from the problems that occur in the field, especially in grade IV SDN 002 Bagan Besar then there needs to be a strategy that can provide learning mathematics is expected to show active learning, creative, effective and fun. This research is tindaan class (PTK), instrument collecting data observation and test learning outcomes. The results obtained: Increased activity of the students from the first cycle to the second cycle are very significant. The increase in active learning, creative, and fun efekif the students also followed by an increase in student learning outcomes. This is evidenced by the increase in the learning outcomes of the first cycle to the second cycle. Namely, from the average value of 88, 27 (cycle I) increased to an average value of 97, 59 (cycle II).